Health Communication in the Context of Student Organizations: A Qualitative Analysis of Group Communication and Mental Health - Give Thanks Keren Hapukh Manalu; Mahela Widya Astutik; Adhelia Candrika Rahmadini (Literasi Nusantara, 2026)
Mental health has become a critical concern for university students, particularly those involved in student organizations who balance rigorous academic demands with organizational responsibilities. Grounded in the framework of health communication, this study examines how organizational communication influences the mental well-being of student group members. A qualitative phenomenological approach was employed, utilizing purposive sampling to select six participants with active experience in university student organizations. Data were collected through in-depth interviews and field observations. The findings reveal that communication within these groups is primarily bidirectional, characterized by openness, mutual respect, and active engagement. Effective communication facilitates seamless information sharing, constructive feedback, conflict resolution, and emotional reassurance. Furthermore, student organizations function as vital support networks, providing encouragement, empathy, and practical assistance to members navigating academic stress or personal challenges. While supportive communication fosters a sense of security, belonging, and comfort, poor communication leads to confusion, interpersonal conflict, and emotional distress. In conclusion, organizational communication plays a pivotal role in safeguarding student mental health within academic and extracurricular environments. Cultivating an organizational culture rooted in open dialogue, empathy, and mutual support establishes a positive environment that enhances overall well-being. These insights underscore the necessity of enhancing health communication strategies within student organizations as a proactive measure to prevent psychological distress and promote holistic student well-being.